Growth and puberty after treatment for acute lymphoblastic leukemia - Alves,Claudia Helena Bastos da Silva (2004)
Over the last 20 years, after combining treatment of chemotherapy and radiotherapy, there has been an improvement in the survival rate of acute lymphoblastic leukemia patients, with a current cure rate of around 70%. Children with the disease have been enrolled into international treatment protocols designed to improve survival and minimize the serious irreversible late effects. Our oncology unit uses the international protocol: GBTLI LLA-85 and 90, with the drugs methotrexate, cytosine, arabinoside, dexamethasone, and radiotherapy. However, these treatments can cause gonadal damage and growth impairment. PATIENTS AND METHOD: The authors analyzed 20 children off therapy in order to determine the role of the various doses of radiotherapy regarding endocrinological alterations. They were divided into 3 groups according to central nervous system prophylaxis: Group A underwent chemotherapy, group B underwent chemotherapy plus radiotherapy (18 Gy), and group C underwent chemotherapy plus radiotherapy (24 Gy). Serum concentrations of LH, FSH, GH, and testosterone were determined. Imaging studies included bone age, pelvic ultrasound and scrotum, and skull magnetic resonance imaging. RESULTS: Nine of the patients who received radiotherapy had decreased pituitary volume. There was a significant difference in the response to GH and loss of predicted final stature (Bayley-Pinneau) between the 2 irradiated groups and the group that was not irradiated, but there was no difference regarding the radiation doses used (18 or 24 Gy). The final predicted height (Bayley-Pinneau) was significantly less (P = 0.0071) in both groups treated with radiotherapy. Two girls had precocious puberty, and 1 boy with delayed puberty presented calcification of the epididymis. CONCLUSION: Radiotherapy was been responsible for late side effects, especially related to growth and puberty.